To be or not to be a Name: Tertium non datur. Cratylus’ Prophecy in Plato’s Cratylus - Botter, Barbara (Revista Archai, 2018)
The name tells the thing if it’s a name. If it doesn’t tell the thing, it isn’t a name. This is the puzzling and enigmatic theory proposed by Cratilo in the homonymous Plato’s dialogue. The thesis in Hermogenes already sounds hermetic, an "oracle" (manteia) which requires the presence of an interpreter to clarify what remains hidden in the terms of the sentence. According to the disciple of Heraclitus, the names are by nature guaranteed to impart pure truths, that is, they are all right (orthous), at least as many as are real names (Cra. 429b11). An imperfectly fitting name isn’t an inappropriate name. It would not be a name at all. In this text we would like to examine the Platonic Cratylus with respect to the meaning that lies behind the words of Cratylus and clarify his position in face of Socrates’s refutation. We will therefore concentrate our attention on the last section of the dialogue devoted to the exchange between Cratylus and Socrates, especially pages 427e-440e.